Karakterisasi dan identifikasi khamir proteolitik dari belacan depik, pasta ikan fermentasi khas Gayo - Eva Murlida; Cut Nilda; Heru Prono Widayat; Murna Muzaifa (AGROINTEK, 2024)
Belacan depik is one of Gayo's fermented fish products, which is still rarely studied scientifically. This product is a fermented fish paste made from depik fish (Rasbora Tawarensis). Scientific studies regarding the yeast involved in the fermentation of depik fish have never been reported. This study aims to characterize and identify yeasts that have proteolytic activity. This study was designed as an exploratory laboratory study, beginning with the isolation and characterization of the yeast from belacan depik and identification molecularly. The three pure isolates Y1, Y2 and Y3 that were successfully isolated had various morphological and biochemical characteristics. Only Y2 isolate has proteolytic activity. The results of molecular recognition showed that isolate B1 was identified as Rhodotorula mucilaginosa strain IMUFRJ 52392 with 100% homology and query cover. The identification of Rhodotorula in belacan depik products indicates a certain role during fermentation. Further studies are needed regarding its role during fermentation and its potential as a biological agent in improving the quality of belacan depik.